Respuesta :
y = -3x + 12...the slope here is -3...a parallel line will have the same slope.
y = mx + b
slope(m) = -3
(-1,6)...x = -1 and y = 6
now we sub and find b, the y int
6 = -3(-1) + b
6 = 3 + b
6 - 3 = b
3 = b
so ur parallel equation is : y = -3x + 3 <==
y = mx + b
slope(m) = -3
(-1,6)...x = -1 and y = 6
now we sub and find b, the y int
6 = -3(-1) + b
6 = 3 + b
6 - 3 = b
3 = b
so ur parallel equation is : y = -3x + 3 <==
a parallel line has a slope equal to original slope. In this case, the parallel line's slope is equal to -3. we use the slope intercept general form of y-y1 = m *(x-x1) in which upon substitution, the form becomes y - 6 = -3 * (x + 1) ; y = -3x + 3. answer is B